1986 y-Walk participants signing in - Unknown:::Creator::::::::::::
Negative shows men, women and children who are particpants in the 1986 y-Walk. They are standing at what are probably sign in tables which are located in a parking lot. There are balloons all along the tables. Some of the people are wearing tee shirts that read: "Walk for women. YWCA 1986." There is a banner that reads: "Start" in the background.